Anatomical characteristics of mandibular lingual foramen: A CBCT investigation - CAI Yongjing; CHEN Zhifang; ZHANG Wei (Kouqiang hemian waike zazhi)
[Objective:] To explore the anatomical characteristics of mandibular lingual foramen (MLF) in different age groups by cone beam computed tomography (CBCT), so as to provide reference for clinical operation to avoid risk. [Methods:] CBCTimages of 280 patients' mandible were selected, including underage group (6-17 years old), young group (18-39 years old), middle-aged group (40-59 years old) and elderly group (over 60 years old), 70 cases in each group. The number, diameter, distribution of the lingual foramen, the distance from the lingual alveolar crest and the shape of the mandibular lingual canal were observed, and the anatomical characteristics between different age groups were compared. [Results:] The high incidence areas of the mandibular lingual foramen were the medial region of the body of mandible and the premolar area. The superior foramen of mental spine in the median area has the highest detection rate and larger diameter. The detection rate of the MLF in the underage group were lower than those in the other three groups. The diameter of lingual foramen in young group was significantly different from that in underage group and elderly group (P<0.01). The diameter of lingual foramen in middle-aged group was significantly different from that in underage group and elderly group (P<0.01), and the clarity of mandibular lingual canal (MLC) wall was positively correlated with age (r=0.141). [Conclusion:] The detection rate of MLF is high, so it is recommended to take CBCT examination before relevant surgery, so as to be familiar with the anatomical structure and avoid serious postoperative complications.